2011
DOI: 10.1016/j.jmacro.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Causality, real estate prices, and the current account

Abstract: a b s t r a c tThis paper explores the causal relations between real estate prices and the current account using recently developed econometric methods for recursive systems. Using a variety of high-quality real estate indices, we find little evidence that current account deficits (capital account surpluses) directly drove real estate prices in the United States, Spain, and Ireland. There is some evidence for this linkage in England; however it is transitory and not persistent. There is also strong evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…4 Based on a large cross-section of countries Kole and Martin (2009) Jinjarak and Sheffrin (2011). They argue that current account deficits were unlikely to directly drive real estate prices in the US, Spain and Ireland.…”
Section: Related Literaturementioning
confidence: 99%
“…4 Based on a large cross-section of countries Kole and Martin (2009) Jinjarak and Sheffrin (2011). They argue that current account deficits were unlikely to directly drive real estate prices in the US, Spain and Ireland.…”
Section: Related Literaturementioning
confidence: 99%
“…both equity and house prices) were the main drivers of US current account fluctuations. Jinjarak and Sheffrin (2011) examined the causality between the real estate and the current account using recent econometric methods for recursive systems. They found little evidence that current account deficits or current surpluses directly drove the real estate prices in the United States, Spain and Ireland.…”
Section: Review Of Findings In Other Countriesmentioning
confidence: 99%
“…According to this model, there is a positive correlation between real estate price appreciation and the current account deficit. According to Jinjarak and Sheffrin (2011), animal spirits and optimism could drive individuals to purchase assets, in turn appreciating their prices, leading to further asset purchases. In Figure 8.2, we show the relationship between the current account and net portfolio flows.…”
Section: Introductionmentioning
confidence: 99%
“…He found that capital inflow shocks significantly push up housing and stock prices. Also, Jinjarak and Sheffrin (2011) studied the link between house prices and the current account. However, they argue that current account deficits were unlikely to directly affect real estate prices in the US, Spain and Ireland.…”
Section: Literature Reviewmentioning
confidence: 99%